EDITING CROSS-CUTTING IN THE FILM HAJI BACKPACKER - Mulia, Prajanata Bagiananda; Dharsono, D., (Seni Media Rekam ISI Surakarta, 2019)
The aim of this research is the revealing the use of editing cross-cutting formed in Haji Backpacker’s film. This research uses qualitative research method: interpretative analysis formalist aesthetics approach, editing cross-cutting of Karel Reisz through Sergei Eisenstein’s montage theory. This research focuses on studying the aesthetic and the application of editing cross-cutting in Haji Backpacker’s film. Editing cross-cutting observed from the forms, functions, relations of themes, and motivation of existence, until analysis of Sergei Eisenstein’s montage, those are metric, rhythmic, tonal, overtonal and intellectual. The results of this research reveals the artistic meanings of Haji Backpacker’s film as formalist aesthetics, and editing cross-cutting’s concepts that formed in Haji Backpacker’s film by Danial Rifki through montage analysis of Sergei Eisenstein.